Bidirectional Underwater Visible Light Communication - Arsyad Ramadhan Darlis; Andre Widura; Muhamad Rifan Andrian (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper, a novel bidirectional underwater visible light communication (BiUVLC) is proposed. The VLC transmitter transmits an information signal using the one of RGB LED through the water tank that represents an underwater environment and then is received by VLC receiver via a color filter. The color LEDs and color filters are utilized in bidirectional systems. The single link is created by a LED on the transmitter and the color filter on the receiver with the same color which represents a single wavelength. The performance of the proposed BiUVLC system was evaluated via implementations. The experimental result shows that the transmitted signal undergoes attenuation over the underwater optical channel and the pair of the blue wavelength in link 1 and the green wavelength in link 2 have the best performance than the other wavelength pair. In the crosstalk measurement, the red wavelength color is the worst in the underwater environment.